Application of The Project Based Learning Model to The Basic Movement Ability of Pencak Silat Step Patterns in Elementary Schools - Syakiro Nikmah; Adang Sudrazat; Muhammad Nur Alif (Universitas Negeri Semarang, 2025)
This study aims to determine the application of the project-based learning (learning PjBL) model to the basic movement skills of step patterns in elementary schools. The method used was quasi-experiment with pre-test and post-test . control group design Students from grade IV at Public Elementary Schools Duri Kosambi 07 Jakarta were divided into two groups: the experimental group (PjBL) and the control group using conventional learning. The test results statistical (Sig. 0.000 <0.05) showed a significant difference between the pretest and posttest results in in both groups, indicating that the PjBL model is effective improving students’ basic movement skills. additionIn, the N-Gain test results showed that the experimental group was . better than the control groupThis study found that the PjBL model encourages students to participate actively, creatively, and collaboratively in improving the basic movement skills of pencak silat step patterns more effectively than conventional methods. Therefore, PjBL can be used as an alternative to innovative physical learning in elementary schools.